Effects of acute caffeine intake on muscular power during resistance exercise: a systematic review and meta-analysis - Xiao, Y.; Ding, L.; Xu, Z.; Liu, J.; Guo, L.; Barnes, M. J.; Cao, Y.; Girard, O. (Frontiers in Nutrition, 2025)
Background: This study examined the effects of caffeine on movement velocity and power output during resistance exercises and explored moderating factors influencing these effects.